Case Report: A 65-year-old man with paraganglioma accompanied by elevated interleukin-6 levels and KIF1B single gene mutation - Wang, Chi; Guan, Ming; Zhang, Shuang; Cui, Can (Frontiers in Endocrinology, 2023)
Paraganglioma is a less prevalent disease, and paraganglioma with only secreting interleukin-6 (IL-6) has not been previously reported. A 64-year-old male patient came to the hospital with the chief complaints of fever and palpitations. The peak body temperature was 38.7°C (101.66°F). Heart rate was 110 bpm, while blood pressure was in the normal range. Antibiotics and antiviral therapies were ineffective. The levels of blood IL-6, C-reactive protein (CRP), alkaline phosphatase (ALP), platelets (PLT), glutamyltransferase (GGT), fibrinogen, and D-dimer were all elevated. Infectious diseases, auto-immune diseases, and hematological malignancy were all excluded. Nearly 10 years ago, a large retroperitoneal mass of the patient was detected by accident. Fortunately, there have been no special symptoms for the past 10 years after regular follow-up. After admission this time, PET-CT was performed. A large confounding density mass at the upper part of the abdominal and retroperitoneal area was seen, and the possibility of paraganglioma was considered. However, biochemical assays for blood and urine catecholamine and their metabolites including adrenaline, norepinephrine, 3-methoxytyramine, methoxyepinephrine, methoxynorepinephrine, and vanillylmandelic acid were all in normal range in spite of mild elevated dopamine with no significance. The whole-exome capture and sequencing of the genomic DNA of the patient showed a heterozygous mutation in the coding site of KIF1B gene (Coding: NM_015047.3:c.4660G>C, Mutation: p.Val1554Leu; chromosomal location was chr1: 10428570). The mutation at this locus of KIF1B has not been reported previously. The patient refused the surgical treatment. Because the mass burdens several important organs including the pancreas, the risk of surgery was high. Doxazosin was then administered to the patient. After taking doxazosin, the symptoms disappeared rapidly. Body temperature returned to normal range in 3 days. Heart rate decreased to approximately 90 bpm. In the following days, the levels of IL-6, CPR, ALP, platelets, GGT fibrinogen, and D-dimer continued to decrease. After 63 days of taking doxazosin, IL-6 level was completely normal. After 190 days of medication, hemoglobin (Hb) and GGT levels also returned to the normal range. After 1 year onset, the patient again underwent a blood test. Almost all blood indexes were in the normal range including IL-6.